End-of-life medical challenges: some reflections on Muslim juridical approaches - Haneef, Sayed Sikandar Shah; Abdul Razak, Mohd Abbas (2017)
Unprecedented advancement in medical technology and its rapidly growing field of allied sciences indisputably have contributed significantly to the treatment of diseases and even inborn defects. However, they challenge many traditionally cherished age-old conceptions about diseases, natural deformities and even end-of-life care. Victims of accidents and those suffering from irrecoverable chronic diseases are put in life-support in the intensive care of the hospital thereby creating a new kind of life and possibility for terminating such a life. Thus, raising topical issues of bioethical import, such as euthanasia and brain death for both the ethicians and jurists to speculate. Both juridical bodies and individual jurists have come hard on active euthanasia but by and large endorsing medical definition of brain death to be in consonance with Islam. This has led critics to question the legitimacy of such juridical pronouncements on larger ethical and metaphysical grounds and propose methodological framework to remedy the situation. This paper, therefore, by engaging with such a discourse argues for a holistic approach to meet the medical challenges of end-of-life care in line with both ethical and legal ethos of Islamic Shari`ah which in principle does not bifurcate legality from morality.